(untitled) (Marketing Jurnali, 2025)
The current article reviews the aspects of digital marketing technologies as well as the key aspects of green marketing within enterprises. Meanwhile, it reflects vital elements of digital marketing and green marketing used by different types of enterprises, organizations and companies.